Long-term analysis of a savings program in elementary school. (December 2022) - Davidson, Jennifer A; Walstad, William B
The prevalence of in-school savings programs (ISSPs) for children and youth is widespread, but research on their effectiveness is limited. This study investigates the long-term effects of an ISSP conducted in one U.S. elementary school. Survey data were collected on the financial behaviors of high school students, who participated in or did not participate in an ISSP while attending the same elementary school at the same time. The results from a probit analysis of data controlling for demographic variables showed that ISSP participants compared with non-participants were more likely to have a bank account in high school. They also were more likely to have opened a bank account before attending high school. Further results show that high school students with bank accounts are more likely to save regularly, indicating that ISSP contributes indirectly to saving regularly through its direct influence on getting students to open a bank account and open it early.